Makna Pengalaman Putus Sekolah Bagi Remaja di Era Digital: Studi Fenomenologi pada Remaja di Desa Cikampek Utara, Kabupaten Karawang - Adi Satria, Arif (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The government has stipulated that everyone should have the right to a proper education. But there are many children who do not fulfill the minimum 9-year compulsory education requirement. Across Indonesia, around 83.7 thousand students dropped out of school in the 2020/2021 academic year based on data collected by the Ministry of Education, Culture, Research and Technology (Kemdikbudristek). Adolescents who drop out of school are at risk of experiencing situational low self-esteem, juvenile delinquency, early marriage, and the loss of a quality generation. The purpose of the study was to gain an in-depth understanding of the meaning of the experiences of adolescents who dropped out of school in the digital era. This study used a qualitative approach with phenomenological methods on five informants in North Cikampek Village, Karawang Regency. The results of the study found 10 themes, namely: Reasons for Dropping Out of School, Use of Cellphone/Gadget/Smartphone, Use of Social Media, Emotional Response, Activities after Dropping Out of School, Decision Making to Drop Out of School, Family Response, Environmental Response, Future Expectations, and Importance of Education.